2011
DOI: 10.1084/jem.20101712
|View full text |Cite
|
Sign up to set email alerts
|

IL-23–responsive innate lymphoid cells are increased in inflammatory bowel disease

Abstract: Increased numbers of innate lymphoid cells in patients with inflammatory bowel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
500
2
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 578 publications
(534 citation statements)
references
References 32 publications
19
500
2
4
Order By: Relevance
“…2). Functional studies with genetically engineered animals and IL 23 p19 and p40 blockers suggested that blockade of these cytokine subunits might effectively suppress intestinal inflammation in mouse models of colitis [98][99][100][101][102][103][104] . In particular, IL 23 inhibition was effective and prevented activation of T cells and innate lymphoid cells and tissue destruction in vivo.…”
Section: T Cellmentioning
confidence: 99%
“…2). Functional studies with genetically engineered animals and IL 23 p19 and p40 blockers suggested that blockade of these cytokine subunits might effectively suppress intestinal inflammation in mouse models of colitis [98][99][100][101][102][103][104] . In particular, IL 23 inhibition was effective and prevented activation of T cells and innate lymphoid cells and tissue destruction in vivo.…”
Section: T Cellmentioning
confidence: 99%
“…In response to IL-23, DCs produce great amounts of IL-6, which activates other innate cells that may mediate tissue destruction (72). In addition, IL-23 stimulates innate lymphoid cells (ILCs) to secrete IL-17, IL-22, and IFN-γ in human colitis (73) and mouse colitis (71). Thus, Opn may contribute to innate colitis via induction of IL-23 in DCs and/or other innate cells.…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal ILC3 can also mediate intestinal pathology in response to transgenic over‐expression of IL‐23 through the release of IL‐17A, IL‐22, IFN‐ γ and GM‐CSF 130. In line with a disease‐causing role of ILC3, Crohn's disease patients exhibit increased frequency of NCR − (NKp44 − CD56 − ) CCR6 + ILC3 and have elevated levels of IL‐17A 131. Hence, in contrast to their protective and homeostatic roles, ILC3 may also take on pro‐inflammatory roles and contribute to tissue damage and inflammation during disease.…”
Section: Ilc3 In Inflammation and Infectionmentioning
confidence: 99%